2014
DOI: 10.1088/0964-1726/23/9/095022
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial characterization of soil-embedded optical fiber for ground deformation measurement

Abstract: Recently fiber-optic sensing technologies have been applied for performance monitoring of geotechnical structures such as slopes, foundations, and retaining walls. However, the validity of measured data from soil-embedded optical fibers is strongly influenced by the properties of the interface between the sensing fiber and the soil mass. This paper presents a study of the interfacial properties of an optical fiber embedded in soil with an emphasis on the effect of overburden pressure. Laboratory pullout tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…The authors concluded that failure of the fibre-soil interface was highly progressive during the deformation process of soil ( Figure 14). Please note that the different behaviour reported in the works of Zhang et al [185,186] is likely due to the particular soil conditions and to the specific friction between cables and soil. The response of optical fibre cables to shear was also investigated many years before by installing the fibre transversally to the direction of slippage [169].…”
Section: Distributed Strain Sensing For Slopes and Landslides Monitoringmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors concluded that failure of the fibre-soil interface was highly progressive during the deformation process of soil ( Figure 14). Please note that the different behaviour reported in the works of Zhang et al [185,186] is likely due to the particular soil conditions and to the specific friction between cables and soil. The response of optical fibre cables to shear was also investigated many years before by installing the fibre transversally to the direction of slippage [169].…”
Section: Distributed Strain Sensing For Slopes and Landslides Monitoringmentioning
confidence: 89%
“…It is important to note that (assuming no slippage between cable and soil) due to the different mechanical behaviour of the fibre-optic cables and characteristic of the surrounding soil, the strain measured in the fibre-optic cable is not that of the soil [184]. Recent work by Zhang et al [185] suggested that overburden pressure, density, and water content of the soil strongly affect the coupling between soil and fibre cable. The experiment was very basic and consisted of measuring the stress exerted on a 900 µε tight buffered fibre, 1 m-long, progressively pulled out from a small soil tank (150 × 20 × 20 cm).…”
Section: Distributed Strain Sensing For Slopes and Landslides Monitoringmentioning
confidence: 99%
“…8, 9, and 10, while the working face passed through the monitoring borehole, the compressive strain of the sensing fiber increased gradually at the drilling depth of 450-580 m. It indicates that the advanced support pressure of the overlying strata increased gradually as well. The strains of the three sensing cables were relatively large at the depth of 490 m, indicating that the strata behaviors induced by mining distributed between the fault zone and the depth of 490 m. Figures 7,8,9,and 10 show that, during the period from July 10 to August 30, the rock strata beneath the bottom of the lower igneous rock layer were compressed by periodic weighting of the overlying rock, and the deformation increased gradually during the mining process. Because the sensing cables have been broken, the strata deformation below the damage points could not be measured anymore.…”
Section: Deformation Of Overlying Stratamentioning
confidence: 99%
“…In the recent years, optical fiber sensing technologies have developed rapidly and are being recognized as a promising monitoring method [7][8][9][10]. The Brillouin optical time-domain reflectometer (BOTDR)-based optical fiber strain sensor has emerged with a variety of advantages, such as distributed and long-distance measurement, corrosion resistance, and anti-electromagnetic interference.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the fiber optic sensing technologies have been advocated for slope monitoring by some scholars [1][2][3][4][5][6][7][8]. Different types of FBG-based in-place inclinometers have been developed, which demonstrated various features, such as small size, superior chemical resistance and stability, immune to electro-magnetic interference, and quasi-distributed monitoring capability [9][10][11][12][13]. This technology is especially suitable for automatic and long-distance monitoring in landslides.…”
Section: Introductionmentioning
confidence: 99%